(untitled) (Journal of Parents and Teachers, 2014)
A group and its way of relating with each other will determine our potential in order to solve conflicts effectively. This is why the author explains here the biology of a group, that is, the seven stages that a group suffers from its initial formation until superior situations of communication; the geography of the group and how the relationships of power are drawn; and finally the geometry of the group or an integrating (or not) model.